Physical Activity and Metabolic Health in New Zealand European and Pacific Women from the Promise Study - Jo Slater; Rozanne Kruger; Nikki Renall; Marilize Richter; Marine Corbin; Wendy J. O’Brien; Leigh Signal; Bernhard H. Breier (Proceedings, 2019)
Background: This study investigates relationships between physical activity (PA) andbiomarkers of metabolic health in populations with different metabolic disease risk; Pacific and NewZealand European (NZE) women with different body composition profiles. [...]